2005
DOI: 10.1681/asn.2004090776
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Uroplakin IIIa Heterozygous Mutations Cause Human Renal Adysplasia Leading to Severe Kidney Failure

Abstract: Human renal adysplasia usually occurs sporadically, and bilateral disease is the most common cause of childhood end-stage renal failure, a condition that is lethal without intervention using dialysis or transplantation. De novo heterozygous mutations in Uroplakin IIIa (UPIIIa) are reported in four of 17 children with kidney failure caused by renal adysplasia in the absence of an overt urinary tract obstruction. One girl and one boy in unrelated kindreds had a missense mutation at a CpG dinucleotide in the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 49 publications
2
97
4
Order By: Relevance
“…All patients were 46 XX with normal gross karyotypes. Clinical summaries of the cases, including those of an individual (patient 6) with a known UPIIIA mutation (20), are shown in Table 1. Note that most had associated malformations of the upper renal tract and over half had impaired renal excretory function.…”
Section: Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…All patients were 46 XX with normal gross karyotypes. Clinical summaries of the cases, including those of an individual (patient 6) with a known UPIIIA mutation (20), are shown in Table 1. Note that most had associated malformations of the upper renal tract and over half had impaired renal excretory function.…”
Section: Patientsmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) amplification and sequencing of all exons plus 100-200 bp of surrounding sequence were performed for UPIIIA (six exons) and SHH (three exons) essentially as described by Jenkins et al (20); for SHH the primers used are those listed in Table 2 and 1× Buffer Q (Qiagen) was included in the reaction for PCR using primers SHH_3c since the 3' end of the gene is G:C rich. For HNF1β (nine exons) sequencing was performed as described (29).…”
Section: Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in UPK3A have recently been found in some patients with renal aplasia, hypoplasia and dysplasia, including some who had vur. 121,122 By contrast, other investigators found no evidence for major involvement of UPK3A in vur, [123][124][125][126] but concede that their results do not rule out mutations in regulatory elements affecting gene expression or function. 123,126 The X chromosome some strong candidate genes on the X chromosome (KAL1 and AGT2R) as well as reports of X-linked transmission and evidence suggesting linkage of primary vur to the pseudoautosomal region 22 led Kelly et al 125 to investigate the possibility of linkage in these areas in a study in 2009.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 85%